2019
DOI: 10.1021/acschembio.9b00458
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into DC-SIGN Binding to Self-Antigens: The Interaction with the Blood Group A/B Antigens

Abstract: The dendritic cell-specific intracellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) is an important receptor of the immune system. Besides its role as pathogen recognition receptor (PRR), it also interacts with endogenous glycoproteins through the specific recognition of self-glycan epitopes, like Le X . However, this lectin represents a paradigmatic case of glycan binding promiscuity, and it also has been shown to recognize antigens with α1−α2 linked fucose, such as the histo b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 40 publications
(83 reference statements)
6
55
0
2
Order By: Relevance
“…Advances in NMR methods hold great potential for direct spatial structure determination of carbohydrate-protein complexes in solution based on intermolecular NOEs which affords estimation of atomic contacts between a protein and a carbohydrate ligand [ 97 , 98 ]. Further extraction of NOE-derived distance restraints for a saccharide molecule results in generation of representative conformational ensembles [ 99 , 100 , 101 ].…”
Section: Carbohydrate 3d Structure Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…Advances in NMR methods hold great potential for direct spatial structure determination of carbohydrate-protein complexes in solution based on intermolecular NOEs which affords estimation of atomic contacts between a protein and a carbohydrate ligand [ 97 , 98 ]. Further extraction of NOE-derived distance restraints for a saccharide molecule results in generation of representative conformational ensembles [ 99 , 100 , 101 ].…”
Section: Carbohydrate 3d Structure Modelingmentioning
confidence: 99%
“…Vast variety of methods provide information about 3D structure of individual glycans and glycan moieties of glycoproteins and protein-carbohydrate complexes ( Figure 6 ) [ 285 , 286 ]. The following approaches are most utilized for 3D structural data validation [ 287 , 288 , 289 ]: Ccombination of carbohydrate simulated geometry data with X-ray crystallographic data analysis [ 225 , 290 ]; Analysis of inter-glycosidic NMR spin couplings, which depend on glycosidic bond torsions [ 114 , 291 , 292 ]; Deriving nuclear Overhauser effects (NOEs) from relative populations of the interatomic distances, with subsequent comparison to the experimental NOEs in solution [ 99 , 293 , 294 ]; Purely informatic detection of errors, such as incompatible atomic coordinates originating from incorrect processing or simulation [ 295 , 296 , 297 , 298 ]; Simulation by other computational methods at higher levels of theory [ 102 , 103 , 105 , 108 ]. …”
Section: Experimental Data Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular human C-type lectins, such as DC-SIGN (dendritic cell specific intercellular adhesion molecule-3 grabbing non-integrin) and MBL (mannose binding lectin), can bind aberrant oligomannosylation, requiring a calcium ion for coordination with the glycan, to facilitate their removal [28]. It has been reported that monosaccharide fucose units can also coordinate with the calcium ion in DC-SIGN and even manifest interaction with α1−α2 linked fucose as presented by histo blood group antigens, highlighting a prime example of the cross-specificity or promiscuity that exists in many lectins [29,30]. There are also several plant and microbe derived lectins that recognize oligomannose units in a calcium independent manner including Pseudomonas fluorescens agglutinin (PFA), which is a member of the Oscillatoria agardhii agglutinin homologue family of lectins capable of recognizing the Man alpha(1-3)-Man alpha(1-6)-Man core [31] present on high mannose and hybrid type glycans.…”
Section: Introductionmentioning
confidence: 99%